2021
DOI: 10.31462/jseam.2021.03196212
|View full text |Cite
|
Sign up to set email alerts
|

Seismic damage assessment of a historical masonry minaret considering soil-structure interaction

Abstract: Historical structures should be carefully preserved and transferred to the next generations. Therefore, their seismic performances should be investigated in detail. In the finite element method, many parameters affect the seismic behaviour and damage distribution in the structures. One of the most significant parameters is the Soil-Structure Interaction effect. In finite element analyses, the soil medium is generally neglected, and the structures' base is restrained by fixed supports. In this study, seismic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…where εc and εt are total strain in compressive and tension conditions, The literature includes limited studies featuring use of a direct soil-structure interaction approach at the damage simulation due to soil settlement on historical structures [23]. There are some studies in the literature that focus on structural behavior of masonry structures taking into account the soil-structure interaction [24][25][26][27][28][29][30][31][32][33][34][35]. On the other hand, there are also studies that take into account the seismic effect and differential settlement effects for historical structures [36][37][38][39][40].…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where εc and εt are total strain in compressive and tension conditions, The literature includes limited studies featuring use of a direct soil-structure interaction approach at the damage simulation due to soil settlement on historical structures [23]. There are some studies in the literature that focus on structural behavior of masonry structures taking into account the soil-structure interaction [24][25][26][27][28][29][30][31][32][33][34][35]. On the other hand, there are also studies that take into account the seismic effect and differential settlement effects for historical structures [36][37][38][39][40].…”
Section: Finite Element Modelmentioning
confidence: 99%
“…It should be stated that, wherever possible, the soil properties were gradually increased from weak soil to hard soil to eliminate the settlement effect. The material properties of the soil domains, which are available in the literature, are also shown in Figure 12 [41][42][43]. As can be seen, the elasticity modulus values changed between 1.14 × 10 9 -5.68 × 10 9 N/m 2 while the density values changed between 1667-2064 kg/m 3 .…”
Section: Numerical Evaluationmentioning
confidence: 99%
“…They concluded that the developed formula for the frequency calculation of stone arch bridges could be used to obtain a reference. Altıok and Demir [13] Altiok and Demir, the seismic behavior of the historical Lala Mehmet Pasha minaret was investigated by considering the Soil-Structure Interaction (SII). The initial finite element (FE) model was updated according to the data obtained from the operational modal analysis (OMA) method.…”
Section: Introductionmentioning
confidence: 99%